Augmented Reality in Medical Practice: From Spine Surgery to Remote Assistance - Cofano, Fabio; Di Perna, Giuseppe; Bozzaro, Marco; Longo, Alessandro; Marengo, Nicola; Zenga, Francesco; Zullo, Nicola; Cavalieri, Matteo; Damiani, Luca; Boges, Daniya J.; Agus, Marco; Garbossa, Diego; et al. (Frontiers in Surgery, 2021)
Background While performing surgeries in the OR, surgeons and assistants often need to access several information regarding surgical planning and/or procedures related to the surgery itself, or the accessory equipment to perform certain operations. The accessibility of this information often relies on the physical presence of technical and medical specialists in the OR, which is increasingly difficult due to the number of limitations imposed by the COVID emergency to avoid overcrowded environments or external personnel. Here, we analyze several scenarios where we equipped OR personnel with augmented reality (AR) glasses, allowing a remote specialist to guide OR operations through voice and ad-hoc visuals, superimposed to the field of view of the operator wearing them. Methods This study is a preliminary case series of prospective collected data about the use of AR-assistance in spine surgery from January to July 2020. The technology has been used on a cohort of 12 patients affected by degenerative lumbar spine disease with lumbar sciatica co-morbidities. Surgeons and OR specialists were equipped with AR devices, customized with P2P videoconference commercial apps, or customized holographic apps. The devices were tested during surgeries for lumbar arthrodesis in a multicenter experience involving author’s Institutions. Findings A total number of 12 lumbar arthrodesis have been performed while using the described AR technology, with application spanning from telementoring (3), teaching (2), surgical planning superimposition and interaction with the hologram using a custom application for Microsoft hololens (1). Surgeons wearing the AR goggles reported a positive feedback as for the ergonomy, wearability and comfort during the procedure; being able to visualize a 3D reconstruction during surgery was perceived as a straightforward benefit, allowing to speed-up procedures, thus limiting post-operational complications. The possibility of remotely interacting with a specialist on the glasses was a potent added value during COVID emergency, due to limited access of non-resident personnel in the OR. Interpretation The possibility to observe directly the operatory theater through the eyes of the surgeon might be a game-changer, giving the possibility to surgeons to be virtually at the site of the operation, both as a trainee or as an expeirenced mentor.